Effect of different weeding regimes on growth, nodulation, and yield performance of Soybean cv. Barisoybean-6 - Islam, Rafiqul; Akter, Tangida; Joy, Fainur; Shamsunnahar, -; Rabbani, Mohammad Golam; Hoshain, Shohrab (Research in Agriculture Livestock and Fisheries, 2021)
The experiment was conducted at Agricultural field laboratory in Noakhali Science and Technology University during the period from mid-January 2019 to 1st week of May 2019, to find out the growth, nodulation, and yield performance of soybean cv. BARI soybean 6 under different weeding regimes. The experiment consists of four treatments viz. T0 (No weeding), T1 (Weed free), T2 (Two hand weeding at 15 DAS and 30 DAS) and T3 (Three hand weeding at 15 DAS, 30 DAS and 45 DAS). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Characters like plant height, number of pod plant-1, number of effective pod plant-1, number of non-effective pod plant-1, number of seed pod-1 and yield varied significantly among the different weeding regimes. The highest seed yield (1.275- ton ha-1) was recorded at T1 (weed free) and the lowest seed yield (0.903-ton ha-1) was observed at T0 (No weeding) condition. The economic analysis of the treatments showed that farmers will be better off by adopting two weeding regimes and weeding at 15 DAS and 30 DAS is therefore recommended for high income. Res. Agric., Livest. Fish.8(2): 193-199, August 2021